The Higher Education Students’ Rights under Martial Law - S. V. Vasyliev (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article is devoted to the problems of legal regulation and peculiarities of exercising students' rights under martial law. The legislative and bylaw acts, works of individual scholars who have studied the problems of legal regulation of the educational process under martial law are studied. The scientific novelty of the study is to identify the peculiarities of exercising the rights of higher education students under martial law and to develop proposals for improving current legislation.